Singing as a Meaningful Learning Approach for Introducing Numbers and Letters in Early Childhood Education - Fajar Tri Nanda Rahayu; Sandie Gunara; Fensy Sella; Salieu Jammeh (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2025)
Purpose: This study aims to describe the effectiveness of a singing-based approach in introducing numbers and letters to early childhood learners at TK Melati Purwakarta. Considering that early childhood cognitive development is characterized by symbolic and imaginative thinking, this period is regarded as a golden age for the introduction of early literacy skills. Method: This study employed a qualitative approach using a descriptive method. Data were collected through classroom observations, interviews, and documentation of learning activities. Results and Discussion: The findings indicate that the singing-based approach enhances children’s ability to recognize numbers and letters in an enjoyable and meaningful way. Songs combined with body movements and visual media were found to improve memory, concentration, and active engagement in the learning process. Teachers implemented learning activities systematically, beginning with the selection of theme-appropriate songs and continuing through to the evaluation of children’s development. In addition to cognitive benefits, this approach also contributed positively to the development of children’s musicality and social-emotional skills. Conclusion: The singing-based approach represents an effective and appropriate alternative teaching method in early childhood education, particularly for introducing numbers and letters in a fun and meaningful manner.